Pengaruh Kepemilikan Keluarga Dan Koneksi Politik Terhadap Pilihan Auditor - Dionisius Adita Putra; Yeterina Widi Nugrahanti (Jurnal Akuntansi dan Pajak, 2023)
This study aims to analyze and provide empirical evidence whether family ownership and political connections can influence auditor choice in manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Research related to the influence of family ownership and political connections on auditor choice is still limited so this research was chosen to be carried out seeing the number of cases of auditor selection errors and causing fatal problems. The sample selection method used purposive sampling technique and found 105 companies with 315 samples. Hypothesis testing used logit regression because the dependent variable was a dummy variable measured by a ratio scale. The results of the study found that family ownership and political connections did influence the selection of auditors. The conclusion is that the cost of using the services of Big 4 Public Accountants is also one of the reasons why companies with high family ownership tend to choose Non- Big 4 Public Accountants.